# 12x - 3y = -3 6x + y = 1Please explain how you got your answer,thanks! :)

Asked on by jgwirki

hala718 | High School Teacher | (Level 1) Educator Emeritus

Posted on

Given the system of equations:

12x - 3y = -3.........(1)

6x  + y  = 1...........(2)

We will use the elimination method to solve.

First, we will multiply (2) by -2:

==> -2 [ 6x + y = 1 ]

==> -12x  -2y = -2......(3)

Now we will add (1) to (3).

==> -5y = -5

Now we will divide by -5

==> y= 1

Now we will substitute into (2) to find x.

==> 6x + 1 = 1

==> 6x = 0

==> x = 0

Then the solution is the pair (x, y) = ( 0, 1)

Jyotsana | Student, Grade 10 | (Level 1) Valedictorian

Posted on

12x-3y=-3    You subtract12 on both side to let the y on one side.

12x-3y=-3+12x

-3y=-3+12x

-3y/-3=-3/-3=12x/3

y=1+6x   You plug this equation on the other equation where y is.

6x+1+6x=1

12x+1=1

12x=0     Divide both side by 12 to let x by itself

12x/12=0/12

x=0

You plug the 0 on where the x is to solve for y.

5(0)+y=1

0+y=1

0+y-0=1-0

y=1

givingiswinning | Student, Grade 10 | (Level 1) Valedictorian

Posted on

12x-3y=-3

12x-3y=-3+12x

-3y=-3+12x

-3y/-3=-3/-3=12x/3

y=1+6x

6x+1+6x=1

12x+1=1

12x=0

12x/12=0/12

x=0

5(0)+y=1

0+y=1

0+y-0=1-0

y=1

jess1999 | Student, Grade 9 | (Level 1) Valedictorian

Posted on

12x - 3y = -3

6x +   y  = 1

First multiply everything in the second equation by 3

By multiplying, you should get

12x - 3y = -3

18x + 3y = 3  now add -3y with 3y ( which means also add 12x with 18x and -3 with 3 )

By adding, you should get

30x = 0 divide both sides by 30

By dividing you should get

x = 0/30 simplify

x = 0 which is your answer for " x "

Now plug 0 into one of the equation

6 ( 0 ) +   y  = 1 Multiply 6 with 0

By multiplying you should get

y = 1 which is your answer for " y "

So your answer is x = 0  ; y = 1

atyourservice | Student, Grade 11 | (Level 3) Valedictorian

Posted on

12x - 3y = -3

6x + y = 1

you can work with any problem first by I am going to work with the first problem first:

Try to get -3y alone by subtracting 12x

-3y = -3 - 12x

now divide by -3 to get y alone:

y = 1 + 4x

now plug this in as y in any of the problems:

6x + 1 + 4x =1

combine like terms

10x = 0

divide by 10

x = 0

now plug in 0 as x to get y

6(0) + y = 1

0 + y =1

y = 1

Wiggin42 | Student, Undergraduate | (Level 2) Valedictorian

Posted on

(1) 12x - 3y = -3

(2) 6x + y = 1

Multiply the (2) by 2

(3) 12x + 2y = 2

subtract (3) from (1)

12x -3y = -3
-
12x + 2y = 2

-5y = -5

Solve for y

y = 1

Plug in the y value for either (1) or (2) and solve for x!

ashwith186 | Student, Grade 9 | eNotes Newbie

Posted on

given eq:-

12x-3y=-3

6x+y=1

by solving these substituting method we get

12x=3y-3

x=(3y-3)/12

x=3(y-1)/3*4

x=(y-1)/4 substitute in6x+y=1

6*(y-1)/2*2+y=1

(3y-3)/2+y=1

(3y-3+2y)/2=1

5y-3=2

5y=5

y=1

(x=y-1)/4

x=0/4=0

******x=0*************

******y=1*************

y=1

We’ve answered 319,190 questions. We can answer yours, too.